The Inhibition Test of Extract Paku Pohon (Cyathea contaminans (Hook.) Copel.) To Fungi Microsporum gypseum In Vitro - Citra Dewi Turnip; Ridwanti Batubara; Herawaty Ginting (Peronema Forestry Science Journal, 2014)
This study aims to determine the effect of inhibition extract paku pohon (Cyathea contaminans (Hook.) Copel.) to fungi Microsporum gypseum, the fungus causes skin disease, horn or keratin-eating substances, as well as damage the nails and hair. The method of the study was in vitro test by paper disc method. The extracts were diluted into concentrations of 500 mg / ml, 400 mg / ml; 300mg/ml; 200mg/ml; 100mg/ml, until 10 mg / ml for M. gypseum tests respectively. Each petri dish added 0.1 ml of inoculum was added 15 ml of Potato Dextrose Agar media that has been thawed sterile and wait until the temperature reaches 4500C, respectively disc subsequent paper that has been soaked in various concentrations of extract for 15 minutes, put on the media , incubated at a temperature of 20-250 ° C for 48 hours. Inhibitory regions surrounding diameter of disc was measured using calipers paper. Tests carried out 3 times. Performed using DMSO4 blank. The results showed a significant effect on paku pohon extract the inhibition of fungal M. gypseum which starts at a concentration of 400 mg / ml and the smallest inhibition at concentrations of 300 mg extract / ml. The smallest concentration is the value of Minimum Inhibitory Concentration (MIC).Keywords: Cyathea contaminans (Hook.) Copel., extract Paku pohon, M. gypseum.